Using ICT as the Tools of Forming the Senior Pupils’ Research Competencies in the Profile Chemistry Learning of Elective Course “Basics of Quantitative Chemical Analysis - Нечипуренко, Павло; Соловйов, Володимир (Pedagogy of Higher and Secondary Education, 2019)
Nechypurenko P.P. and Solovyov V.M. Using ICT as the Tools of Forming the Senior Pupils’ Research Competencies in the Profile Chemistry Learning of Elective Course “Basics of Quantitative Chemical Analysis. Aims of the study: to substantiate possibilities of the research competencies formation among senior pupils in terms of profile Chemistry learning by means of practical using information and communication technology while accomplishing an elective course “Basics of quantitative chemical analysis”. This research considers the influence of various ICT tools on the formation of individual study and research competencies, in particular the system components of the research competencies among senior pupils in terms of profile Chemistry learning and the methods of their practical applying while accomplishing an elective course “Basics of quantitative chemical analysis”. Object of the study: ICT tools for Chemistry learning. Subject of the study: ICT tools of research competencies formation among senior pupils in terms of profile Chemistry learning. Methods of the study: reviewing and analyzing scientific publications, expert evaluation, summarizing pedagogical experience. Results of the study: the system of research competencies formation among senior pupils is effectively provided by the correct selection of ICT tools and conditions of their applying for the certain research competence formation, which embodies system components. Our research confirms the idea that the most ICT tools are to be leading in the development of research competencies among senior pupils in profile Chemistry learning. They are successfully tested by means of their applying in the process of studying the elective course “Basics of Quantitative Chemical Analysis”. They show the high effectiveness. Our study confirms that virtual chemical laboratories are the most universal and influential tools of forminghe research competencies among senior pupils in profile Chemistry learning.